2018
DOI: 10.1523/jneurosci.2640-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Challenge to Promote Change: The Neural Basis of the Contextual Interference Effect in Young and Older Adults

Abstract: Motor performance deteriorates with age. Hence, studying the effects of different training types on performance improvement is particularly important. Here, we investigated the neural correlates of the contextual interference (CI) effect in 32 young (YA; 16 female) and 28 older (OA; 12 female) human adults. Participants were randomly assigned to either a blocked or a random practice schedule, practiced three variations of a bimanual visuomotor task over 3 d, and were retested 6 d later. Functional magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
(35 reference statements)
3
24
1
Order By: Relevance
“…More specifically, a decrease in GABA levels is indicative of a release from inhibition to promote mechanisms of long-term potentiation, cortical plasticity and learning [ 6 , 8 ]. Whereas previous work reported this GABA modulation to occur in the motor cortex [Floyer-Lea A, et al 2006] we observed it in the broader occipital territory, containing brain areas involved in processing of the stimulus structure and the movement-generated visual feedback, made available during practice (such as primary and secondary visual cortex and posterior precuneus), as exemplified by task-related functional magnetic resonance imaging [ 7 ]. Conversely, the less demanding blocked-practice schedule consisted of repeated presentation of stimuli, resulting in attenuated neuronal responses (repetition suppression) and enhanced GABA levels.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…More specifically, a decrease in GABA levels is indicative of a release from inhibition to promote mechanisms of long-term potentiation, cortical plasticity and learning [ 6 , 8 ]. Whereas previous work reported this GABA modulation to occur in the motor cortex [Floyer-Lea A, et al 2006] we observed it in the broader occipital territory, containing brain areas involved in processing of the stimulus structure and the movement-generated visual feedback, made available during practice (such as primary and secondary visual cortex and posterior precuneus), as exemplified by task-related functional magnetic resonance imaging [ 7 ]. Conversely, the less demanding blocked-practice schedule consisted of repeated presentation of stimuli, resulting in attenuated neuronal responses (repetition suppression) and enhanced GABA levels.…”
mentioning
confidence: 50%
“…A retention test was carried out 6 days later. With MRS, we determined the GABA levels before and after training in primary sensorimotor cortex and occipital cortex, because our previous work showed considerable brain activity in both visual and motor processing regions, in agreement with the unique visuomotor signature of this tracking task [ 7 ]. We found that (1) the behavioral data confirmed the typical contextual interference effects, i.e., random as compared to blocked practice led to temporary inferior performance levels during the acquisition phase but superior skill retention in both age groups, (2) the MRS data demonstrated a training-induced decrease in occipital GABA level during random practice but an increased GABA level during blocked practice and this effect was even more pronounced in older adults [ 6 ].…”
mentioning
confidence: 71%
“…These results point to more efficient retrieval of motor memory due to variable practice (Lin et al, 2011). More complex bimanual visuomotor tasks that were practiced randomly have shown modality-specific activation patterns that led to the recruitment of areas related to visual processing (Pauwels et al, 2018). The effect of variable practice might be related to the strong link between the neuromodulatory systems that control neuronal plasticity and novelty, for instance, the dopaminergic (Redgrave and Gurney, 2006), cholinergic (Hasselmo et al, 1996), and noradrenergic systems (Vankov et al, 1995), which are used by the brainstem activation system for controlling the global state of arousal (Gur et al, 2007).…”
Section: Variable Practicementioning
confidence: 75%
“…The result of several studies has shown that the random practice results in poorer performance during acquisition but superior performance during retention and transfer compared to the blocked practice (Shea and Morgan, 1979;Magill and Hall, 1990;Brady, 1998). The result of studies has also indicated that older adults may benefit from this type of practice condition like younger performers (Lin et al, 2010(Lin et al, , 2012Pauwels et al, 2015Pauwels et al, , 2018Sidaway et al, 2016;Chalavi et al, 2018). However, some studies did not show the superior performance of random practice during retention in older adults (de Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%